THE EFFECTIVENESS OF COLLABORATIVE STRATEGIC READING (CSR) FOR TEACHING READING COMPREHENSION AT MUHAMMADIYAH UNIVERSITY OF SIDOARJO - Novita, Dian (Educate, 2012)
Dian Novita Universitas Muhammadiyah Sidoarjo dheenov@yahoo.com Abstract The study deals with the effectiveness of Collaborative Strategic Reading (CSR) strategy in teaching reading comprehension. The strategy is the combined-strategies instruction that draws on both reciprocal teaching and cooperative learning. Specifically, the study is aimed at finding out the significant improvement of students’ reading comprehension achievement after being taught using Collaborative Strategic Reading (CSR). Based on the calculation of a t-test, the results show that there is a significant improvement in the students’ achievement after they got treated using Collaborative Strategic Reading (CSR) strategy when studying reading comprehension in the classroom. The t-test indicates that the score of the tvalue is higher than ttable (2.18 > 2.021). Here, the experimental group represents a better improvement after they received the treatment. Key words: Collaborative Strategic Reading (CSR), Reading Comprehension Abstrak Penelitian ini berhubungan dengan keefektifan strategi Collaborative Strategic Reading (CSR) dalam pengajaran membaca. Strategi ini merupakan kombinasi dari dua strategi reciprocal teaching dan cooperative learning. Secara khusus, penelitian ini bertujuan untuk mengetahui apakah terdapat peningkatan kemampuan membaca mahasiswa secara signifikan setelah belajar dengan menggunakan Collaborative Strategic Reading (CSR).Berdasarkan perhitungan dengan menggunakan t-test diketahui bahwa terdapat peningkatan kemampuan membaca mahasiswa secara signifikan setelah belajar dengan menggunakan Collaborative Strategic Reading (CSR). Hal ini dibuktikan dengan nilai thitung lebih tinggi dibandingkan ttabel (2.18 > 2.021). Dapat disimpulkan bahwa kelas eksperimental mengalami peningkatan setelah menggunakan strategi Collaborative Strategic Reading (CSR) dalam belajar reading comprehension. Kata Kunci: Collaborative Strategic Reading (CSR), pemahaman membaca